Kritische reflectie op liturgisch ritueel in heden en verleden. Een bijdrage vanuit de ritual studies - Tongeren, Louis van (Jaarboek voor liturgieonderzoek, 2013)
Because rituals are of fundamental importance for understanding cultures and for understanding religion as a central component within cultures, it is very important to also approach the history of culture and religion, and thus the history of liturgy as well, from a ritual perspective. Our interpretation of liturgy in history cannot disregard the behav-ior of people as inspired by liturgical rituals. It is therefore desirable to study the history of liturgy from the angle of its rituality as well. Ritual studies show us that this is no easy task due to the complexity of rituals, caused by interference from a great many factors and a great variety of factors as well. We are already confronted with this com-plexity when we study actual ritual practice, but the complexity only increases when we investigate the form, the execution and the meaning of rituals in history.